DEVELOPMENT OF SKILLS OF TEACHERS AND PARENTS IN TK QURROTA A’YUN USING SEMPOA - Andri Rahadyan; Nia Gardenia; Halimatussa'diah Halimatussa'diah; Muslihatul Hidayah (JMM (Jurnal Masyarakat Mandiri), 2020)
In the conditions at TK Qurota A'yun, the team found that there were several children who had trouble using additional and subtraction operations. Teachers don't even understand how to use abacus for counting. In order to address these issues, the solution proposed in this community service was to provide instruction in the use of arithmetic abacus media to teachers and parents at TK Qurrota A'yun in order to improve the children's abilities, such as raising the ability to count faster, integrating left and right brain use, improving the level of critical thinking and correct analytical thinking, and enhancing concentrative thought. Observation, debate, recording, presentation and practice were the approaches used. The purpose of this community service project was to help teachers gain new insights into the usage of abacus technology, so that they would have more resources in the use of educational media, and teachers would be able to help students learn to rely more easily on adding and subtraction operations.